Confessing the Deaf: A Visual and Material Approach to Religion and Disability in Belgium, c. 1750-1850 - Hofman, Elwin (Svensk teologisk kvartalskrift, 2025)
In eighteenth-century Belgium, a peculiar technique was developed to allow deaf people to take the sacrament of Confession. Religious teachers drew or had them draw the different sins they could commit from a model. These drawings were put together in a book, which the deaf person had to take to their confessor. They could then point to the sins they had committed and receive penance and absolution. We have located twenty of these books, all created between the mid-eighteenth and the mid-nineteenth century, a period in which education of deaf people was in-creasingly professionalizing and institutionalizing. In the context of schools for the deaf, teaching through images was controversial. In practice, however, the methods using images continued to be used, as not everyone could afford the expensive schools that provided more advanced deaf education. The confessional aids complicate the "auricular" in auricular confession and show how the ritual could play to different senses when needed. Its essence lay in the acknowledgment of sins and in penitence, not in the verbal recitation of sins.